2018
DOI: 10.1080/20008198.2018.1472989
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional mindfulness mediates the relationships of parental attachment to posttraumatic stress disorder and academic burnout in adolescents following the Yancheng tornado

Abstract: Background: Previous studies have shown that parental attachment is associated with low severity of posttraumatic stress disorder (PTSD) and low academic burnout in individuals who have experienced traumatic events. Objective: The present study investigated the ways in which parental attachment is related to PTSD symptoms and academic burnout in Chinese traumatized adolescents by considering the role of dispositional mindfulness. Method: A total of 443 Chinese adolescents who had experienced a severe tornado o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…All items were reversely scored to compute a composite score such that higher scores indicate higher levels of mindfulness. This scale has shown good reliability and construct validity in Chinese adolescent samples (An et al, 2018a;Yuan et al, 2018). In the present study, the scale demonstrated good internal consistency (α T1/T2 = 0.92/0.91).…”
Section: Methodssupporting
confidence: 56%
“…All items were reversely scored to compute a composite score such that higher scores indicate higher levels of mindfulness. This scale has shown good reliability and construct validity in Chinese adolescent samples (An et al, 2018a;Yuan et al, 2018). In the present study, the scale demonstrated good internal consistency (α T1/T2 = 0.92/0.91).…”
Section: Methodssupporting
confidence: 56%
“…Another study by Joubert, Webster, and Hackett (2012) found that among maltreated adolescents referred for psychological services, fearful or unresolved attachment predicted PTSS through compromised working memory. Relatedly, dispositional mindfulness was supported to partially mediate the link between attachment and PTSS among Chinese adolescents exposed to a severe tornado (An et al, 2018).…”
Section: Resultsmentioning
confidence: 96%
“…Several findings are worth highlighting. Notably, greater attachment anxiety has been found to predict heightened risk of PTSS among a variety of populations, including but not limited to, the following: intimate partner violence survivors (e.g., Lilly & Lim, 2013), persons exposed to terrorist attacks (e.g., Fraley, Fazzari, Bonanno, & Dekel, 2006), survivors of childhood trauma (e.g., Busuito, Huth-Bocks, & Puro, 2014), Holocaust survivors (e.g., Cohen, Dekel, & Solomon, 2002), prisoners of war (POWs; e.g., Dieperink, Leskela, Thuras, & Engdahl, 2001), security employees (e.g., Bogaerts, Kunst, & Winkel, 2009), torture victims (e.g., Kanninen, Punamäki, & Qouta, 2003), combat veterans (e.g., Ghafoori, Hierholzer, Howsepian, & Boardman, 2008), therapists with vicarious exposure (e.g., Marmaras, Lee, Siegel, & Reich, 2003), persons exposed to natural disasters (e.g., An, Yuan, Liu, Zhou, & Xu, 2018), survivors of motor vehicle accidents (e.g., Andersen, Elklit, & Vase, 2011), clinical populations (e.g., Karatzias et al, 2018), and trauma-exposed college students (e.g., Shallcross, Frazier, & Anders, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies presented additional cross-sectional analyses of the same sample at three [ 53 ], six [ 39 , 47 , 51 ], nine [ 39 , 47 ], and 12 [ 39 ] months post-tornado, each exploring a slightly different conceptual model. In addition, several other studies appeared to use overlapping samples [ 46 , 50 , 52 , 54 ]. Most of these studies presented mental disorder prevalence estimates among children who were exposed to the climate-related disaster but did not compare prevalence at different levels of exposure.…”
Section: Resultsmentioning
confidence: 99%